Isolasi dan Karakterisasi Plant Growth Promoting Rhizobacteria dari Perakaran Kelapa Sawit pada Lahan Gambut - Ariyani, Mei Dwi; Dewi, Tirta Kumala; Pujiyanto, Sri; Suprihadi, Agung (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2021)
Peatlands have characteristics of low pH and lack nutrients. Oil palm is the main plant commodity in peatland management. Oil palm roots have been known to be a nutrition source for the growth of soil microbes, especially bacteria around their roots or PGPR. PGPR are a group of bacteria that play an important role in supporting plant growth and health. The purpose of this research was to obtain PGPR potential from oil palm roots which can be used as candidates for biofertilizer agents. In this study, the isolation and selection of PGPR isolate from oil palm roots on oil palm plantations in Central Kalimantan were carried out based on their plant growth-promoting traits, including the activity of producing Indole Acetic Acid (IAA), phosphate solubilizing, N-fixing, K solubilizing, siderophore production, ACC deaminase activity, proteolytic activity, cellulolytic activity, and ligninolytic activity. A total of 17 isolates were selected to be tested for their multiple activities ability. The final results of the PGPR characterization showed that of the seventeen isolates, all isolates had PGPR activity at least three different abilities. From the seventeen isolates, it was found that the SW 5.5 PK 3A isolate had the highest IAA production activity (58,50 ppm), SW 4.10 PK 1A isolate had the highest K solubilizing index (3,16), SW 8.5 PK 1A isolate had both the highest P solubilizing index (3,73) and the highest siderophore zone index (5,20), SW 4.11 PK isolate had the highest proteolytic index (4,80), and SW 4.10 PK 1A.P isolates had the highest cellulolytic index (5,11).